(untitled) (World Bulletin of Management and Law, 2022)
This study aimed to identify the effect of the quality of accounting reports on the decision to invest in joint-stock companies. The descriptive approach was obtained, and 50 investors in joint-stock companies in Baghdad were assigned as the sample of the study. An 18-items questionnaire was used as tool for data collection. The questionnaire was divided into three sections. The results of the study indicated that investors in joint-stock companies in Baghdad have been impacted significantly by the quality of accounting reports in making their decisions regarding buying and selling shares in joint stock companies. Hence, the quality of accounting reports greatly affects investors’ investment decisions. Furthermore, the findings revealed that investors in joint stock companies in Baghdad reported that the quality of accounting reports is clear, understandable and sufficient for making investment decisions. Moreover, the study showed that investors in joint-stock companies in Baghdad rely on accounting reports when making their investment decisions. Finally, the investors in joint stock companies in Baghdad indicated that the accounting reports are widely available, appropriate and sufficient for them. The study recommended the need to continuously improve the quality of the accounting reports published by the joint stock companies in Baghdad and to make them accessible to all investors who need them. The study also indicates to raise the awareness among investors in joint stock companies on the importance of accounting reports when they make investment decisions.